More than Just Host Plant Preferences for the Two Main Vectors of Xylella fastidiosa in Europe: Two Insect Species and Two Different Behaviors - Saúl Bernat-Ponce; Rosalía García-García; Cristina M. Aure; Lorena Nieves; Juan Pedro Bouvet; Francisco J. Beitia; César Monzó (Insects)
Xylella fastidiosa is a vector-borne bacterium causing significant economic losses in global agricultural industries. Management strategies focus primarily on controlling vector populations. The diversity of vector species, their polyphagy, and the wide range of host plants supporting bacterial development make X. fastidiosa pathosystems particularly challenging to manage. Understanding vector and host plant relationships is key to developing effective strategies. This study examined the oviposition strategies, host preferences, and nymphal development of Europe’s main X. fastidiosa vectors, Philaenus spumarius and Neophilaenus campestris, under semi-field conditions (screenhouse). The two species exhibited distinct behaviors. Neophilaenus campestris primarily laid eggs on its preferential host, the grass Festuca arundinacea, while P. spumarius preferred dry soil substrates, irrespective of the host plant species. The presence of multiple hosts reduced the oviposition rates of P. spumarius compared with single-host scenarios. The nymphs of P. spumarius quickly identified and settled on preferential hosts, while the N. campestris nymphs initially moved randomly but later congregated on their preferred host. Despite their polyphagy, nymph survival was limited to preferential hosts. These findings highlight opportunities for habitat management strategies, such as enhancing plant diversity and eliminating overwintering egg sites, to mitigate vector populations and limit the spread of X. fastidiosa.